Minimax LQG control - Petersen, Ian R. (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an overview of some recent results concerning the emerging theory of minimax LQG control for uncertain systems with a relative entropy constraint uncertainty description. This is an important new robust control system design methodology providing minimax optimal performance in terms of a quadratic cost functional.
Keywords: stochastic uncertain system; minimax control; LQG control; risk-sensitive control; output-feedback control; robust control